Pharmacovigilance study on old drugs repurposed for rare diseases across different indications: the case of fenfluramine - Zhong, Jiahong; Lin, Zhuomiao; Xue, Junling; Yu, Xihui (Frontiers in Pharmacology, 2025)
ObjectiveAs an old drug with a new application in rare diseases with epileptic symptoms, fenfluramine may have potential unrecognized adverse events. Because limited real-world data exist on Lennox-Gastaut syndrome (LGS) and Dravet syndrome (DS) populations, some rare adverse events (AEs) are easily overlooked. The purpose of this study was to comprehensively evaluate the characteristics of adverse events of fenfluramine.MethodsThe data were extracted from the Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) database from the third quarter of 2020 to the fourth quarter of 2024 for data cleaning and analysis. To ensure the accuracy and reliability of the study, adverse events of fenfluramine were analyzed using the Reporting Odds Ratio (ROR), Bayesian Confidence Propagation Neural Network (BCPNN), Proportional Reporting Ratio (PRR), and Multi-Item Gamma Poisson Shrinker (MGPS) methods.ResultsFollowing data deduplication and screening, a total of 9,868 fenfluramine-related adverse event reports were included in this study. The analysis showed that fenfluramine-induced AEs occurred across 24 system organ classes (SOCs). In addition to the typical side effects such as seizure, somnolence, lethargy, status epilepticus, balance disorder and sedation, it is important to pay attention to emerging risks such as pericardial effusion, crying, pneumonia, oxygen saturation decreased, muscle twitching, insomnia, aggression, agitation, mood swings, urinary retention and aortic dilatation. It is notable that aortic valve incompetence and epilepsy are more likely to occur in males and females are more prone to encountering nervous system adverse reactions after fenfluramine treatment. LGS had higher risk after fenfluramine treatment in mitral valve incompetence, constipation, urinary tract infection, fall, lethargy and atonic seizures, while DS had higher risk in pyrexia, illness, nasopharyngitis, influenza, decreased appetite, seizure, generalized tonic-clonic seizure, status epilepticus, myoclonic epilepsy, aggression.ConclusionThis study provided valuable evidence on the real-world safety of fenfluramine, suggesting that clinicians should place greater emphasis on monitoring its adverse effects during use. Medical staff should pay more attention to cardiac AEs on LGS patients and nervous system AEs on DS patients throughout the entire duration of fenfluramine treatment.